2020
DOI: 10.20944/preprints202009.0382.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of the Adverse Effects of Chronic Exposure of Donepezil (An Acetylcholinesterase Inhibitor) in Adult Zebrafish by Behavioral and Biochemical Assessments

Abstract: Donepezil (DPZ) is an acetylcholinesterase inhibitor used for the clinical treatment of mild cognitive impairment. However, DPZ has been reported to have adverse effects, including abnormal cardiac rhythm, insomnia, vomiting, and muscle cramps. However, the existence of these effects in subjects without Dementia is unknown. In this study, we use zebrafish to conduct a deeper analysis of the potential adverse effects of DPZ on the short-term memory and behaviors of normal zebrafish by performing multiple behavi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 92 publications
(107 reference statements)
0
9
0
Order By: Relevance
“…Therefore, automated quantification methods, like those described in the protocols in this article, are required for toxicant screening. Furthermore, the phenotypic assays described can be coupled with biochemical or genomic assays to better characterize the responses to chemicals and connect the behavioral responses to molecular changes (Audira et al., 2021; Audira et al., 2020; Malhotra et al., 2020). In addition, a recent study demonstrated the compatibility of these behavior tests on medaka, another teleost fish (Audira et al., 2021), expanding their applicability.…”
Section: Commentarymentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, automated quantification methods, like those described in the protocols in this article, are required for toxicant screening. Furthermore, the phenotypic assays described can be coupled with biochemical or genomic assays to better characterize the responses to chemicals and connect the behavioral responses to molecular changes (Audira et al., 2021; Audira et al., 2020; Malhotra et al., 2020). In addition, a recent study demonstrated the compatibility of these behavior tests on medaka, another teleost fish (Audira et al., 2021), expanding their applicability.…”
Section: Commentarymentioning
confidence: 99%
“…Based on a prior study, the sex of the conspecifics does not appear to significantly affect the social interaction frequency of the test fish (Audira et al., 2018). However, the use of conspecifics of a similar size, morphology, and coloration to the test fish is recommended (e.g., if the test fish is an absolute mutant zebrafish—fish carrying ednrb1a b140 and mitfa b692 , which exhibits a transparent body appearance—use an absolute mutant zebrafish as its conspecific; Audira et al., 2020). Social interaction in this method is defined as the area in front of the transparent separator up to 3 cm.…”
Section: Commentarymentioning
confidence: 99%
See 3 more Smart Citations